The emergence of the RMB: A "New Normal" for China's exchange rate system? - Frederik Kunze; Tobias Basse; Christoph Wegener; Markus Spiwoks (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
We investigate RMB pricing differentials for onshore and offshore trading. Testing for long memory, we find strong persistence in the pricing differential. Hence, the Chinese FX market in its bipolar structure still lacks basic conditions for perfectly integrated markets.
Keywords: F31; F33; G18; C58; 330; CNY; CNH; RMB internationalization; Market integration; Emerging markets